Character Education Based on Islamic Local Wisdom: A Case Study of Aswaja Value Internalization in a Madrasah Aliyah - Fahrurrozi Fahrurrozi; Mujamil Qomar; Sokip Sokip (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study explores the internalization of Ahlussunnah wal Jama’ah (Aswaja) values in character formation at Madrasah Aliyah Ta’limuasyibian, Pandan Indah Village. Using a qualitative case study approach, data were collected through interviews, participant observation, and document analysis. Findings reveal that Aswaja values—such as moderation (tawasuth), tolerance (tasamuh), balance (tawazun), and social responsibility (amar ma’ruf nahi munkar)—are systematically embedded in curricular activities, school culture, and daily student interactions. These values are integrated not only in religious subjects but also across general lessons, extracurricular religious rituals, and peer interactions. Key challenges include limited teacher training, insufficient contextual teaching resources, and external influences from digital media. Nevertheless, strong community engagement, exemplary leadership from teachers, and active student participation enhance the internalization process. The study highlights the significance of character education rooted in Islamic local wisdom as a strategic response to the moral challenges faced by youth in the digital age